A Case Study Involving U-47700, Diclazepam and Flubromazepam—Application of Retrospective Analysis of HRMS Data. Issue 9 (26th June 2018) - Partridge, Emma; Trobbiani, Stephen; Stockham, Peter; Charlwood, Cheryl; Kostakis, Chris
Abstract: The number of new psychoactive substances (NPS) available is constantly increasing, making it difficult for toxicology laboratories to keep screening methods up to date. Full scan high-resolution mass spectrometry (HRMS) is a versatile technique which allows for progressive updating of spectral databases to increase the scope of screening. It also allows for retrospective screening of data—specifically, reprocessing of data files using an updated spectral database without the need for re-extraction or reanalysis. The coronial case reported here illustrates the application of retrospective processing of HRMS data in the detection of emerging NPS. A 28-year-old male with a history of illicit drug use was found deceased at home. Initial routine screening of the post-mortem peripheral blood identified only methylamphetamine, amphetamine and trace amounts of lorazepam. A compound with an accurate mass and isotope ratio consistent with the opioid AH-7921 was also detected in the liquid chromatography (LC)–HRMS screen; however; the retention time and mass spectrum did not match the library. Further investigation confirmed the compound to be U-47700, another opioid and structural isomer of AH-7921. Several months later, after additional NPS had been added to the in-house HRMS database, retrospective screening of the HRMS data was performed, revealing the presence of designer benzodiazepines, diclazepam and flubromazepam as well as the psychedelic drug 2, 5-dimethoxy-4-chloroamphetamine (DOC). Quantitative analysis gave the following results in peripheral post-mortem blood: U-47700 (330 μg/L), diclazepam (70 μg/L), flubromazepam (10 μg/L), methylamphetamine (290 μg/L) and amphetamine (150 μg/L) (DOC not quantitated). These substances, along with lorazepam and etizolam, were also confirmed in the post-mortem urine and an investigation into blood and urinary metabolites was carried out. All analyses were performed using the same LC–quadrupole-time of flight method. The cause of death was aspiration (of gastric content into airways and lungs) due to mixed drug toxicity.